Association between residence at birth and addiction service utilization: a spatial analysis of the Massachusetts birth record cohort - Xia, Yingjing; Villanueva, Carolina; Vieira, Verónica M. (Frontiers in Epidemiology, 2025)
IntroductionSubstance use disorders impact a significant portion of the US population. Exposure to neighborhood environment early in life may contribute to disparities in policing, health outcomes and access to treatment for substance use disorders. Although many studies have examined the relationship between neighborhood context and substance use, few studies have accounted for the spatial distribution of substance use and social environment. The current study examined the association between birth address and substance addiction service utilization of individuals born in communities around the New Bedford Harbor Superfund site in southeast Massachusetts that face potential racial, socioeconomic, and environmental stressors.MethodsThe analysis utilized birth record data between January 1992 and December 1998 (N = 12,151) from the Registry of Vital Records and Statistics with follow-up for substance addiction service utilization through June 2022 by the Bureau of Substances Addiction Services within the Massachusetts Department of Public Health (MADPH). We used generalized additive models (GAM) with a smooth for location to estimate local odds ratios (ORs) and 95% confidence intervals (CI) of substance addiction service utilization while adjusting for sociodemographic risk factors to identify important contributors to geographic disparities.ResultsWe found that birth addresses were significantly associated with substance addiction service utilization as a young adult (p = 0.037), with the highest statistically significant risk located closest to the harbor (OR = 1.42, 95% CI: 1.00, 2.02). Family education and prenatal care payer were significant predictors (p < 0.001) of substance addiction services use and strong spatial confounders.DiscussionThe current study showed that significant associations between birth addresses and substance addiction service utilization later in life are primarily driven by socioeconomic predictors including family education and prenatal care payer.